Community Structure Detection Algorithm Based on the Node Belonging Degree - Jian Li; Huiwen Deng (Institute of Advanced Engineering and Science, 2013)
In this paper, we propose a novel algorithm to identify communities in complex networks based on the node belonging degree. First, we give the concept of the node belonging degree, and then determine whether a node belongs to a community or not according to the belonging degree of the node with respect to the community. The experiment results of three real-world networks: a network with three communities with 19 nodes, Zachary Karate Club and network of American college football teams show that the proposed algorithm has satisfactory community structure detection. DOI: http://dx.doi.org/10.11591/telkomnika.v11i12.3694